PENANAMAN FALSAFAT ADAT TERNATE “JOU SE NGOFA NGARE” SEBAGAI SUMBER BELAJAR SISWA SMA NEGERI 6 PROVINSI MALUKU UTARA - Zulkifli, Zulkifli; Tomagola, Leny MS (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The purpose of the study on the Ternate Customary Philosophy "Jou Se Ngofa Nagare" is to find out to what extent students of SMA Negeri 6 North Maluku Province can understand and comprehend the values ​​contained and used as a guideline for daily life because these values ​​have a relationship between humans and humans and humans with the creator of the universe. Because a person's thoughts or reflections on themselves and the universe that has been created by God Almighty, from all its contents have their own meanings. The Ternate Customary Philosophy "Jou Se Ngofa Nagare" is part of this cultural value to maintain peace in social, political, economic and cultural life so that the younger generation in this case students are not influenced by various developments of the times that can damage the order of local wisdom values, if the younger generation does not preserve cultural and cultural values, then a regional identity will be lost which has local wisdom that has been inherited by the ancestors in the land of Zajirah Al'mulk or the land of kings. Because the value of local wisdom is part of the socio-cultural capital to maintain human development to preserve the value of local wisdom contained in the Ternate Customary Philosophy "Jou Se Ngofa Nagare" is part of the identity and order towards a better future life, synergy is needed between the young generation and the community to build a commitment to maintain and preserve local culture in formal, informal and non-formal education.